Annual economic burden of hepatitis B virus‐related diseases among hospitalized patients in twelve cities in China. Issue 3 (10th December 2015) - Zhang, S.; Ma, Q.; Liang, S.; Xiao, H.; Zhuang, G.; Zou, Y.; Tan, H.; Liu, J.; Zhang, Y.; Zhang, L.; Feng, X.; Xue, L.; et al.
Summary: A nationwide survey of hepatitis B virus (HBV)‐associated economic burden has not previously been performed in China. The purpose of this study was to examine the direct, indirect, and intangible costs of HBV‐related diseases within the span of one year. A random sample was taken from specialty and general hospitals across 12 cities in six provinces of China. Intangible costs were estimated based on willingness to pay or open‐ended answers provided by patients. The results showed that 27 hospitals were enrolled, with a sample population of 4726 patients (77.7% response rate). The average annual costs were 4454.0 (direct), 924.3 (indirect), and 6611.10 (intangible), corresponding to 37.3%, 7.7%, and 55.1% of the total costs, respectively. The direct medical fees were substantially greater than the non‐medical fees. Annual indirect costs were divided into outpatient (112.9) and inpatient (811.40) loss of income. The intangible costs of chronic HBV were notably higher than either the direct or indirect costs, consistent with the social stigma in China. The comparison amongst individual cities for the average ratio of direct to indirect costs revealed that the sizes of ratios were negatively correlated with the socioeconomic status of the regions. This study suggested that as a whole in China, the HBV‐related diseases caused a heavy financial burden which was positively associated with disease severity. Although the intangible costs coincided with a high prevalence of discrimination against CHB patients in Chinese society, our study may serve as future reference for detailed exploration.